Gardens of a Chinese emperor : imperial creations of the Qianlong Era, 1736-1796 - Siu, Victoria M. Cha-Tsu (Lehigh University Press, 2013)
Qianlong's Yuanming Yuan (Garden of Perfect Brightness) was a microcosm of his world, with lush plants, artificial mountains and lakes, and colorful buildings. From within these precincts, the emperor ruled his lands, performed imperial rituals, and observed various religious ceremonies of his people. Destroyed and looted in 1860 by Western forces, it is today only partially restored. Using images, maps, and color-plates, this book reveals the philosophical, political, and artistic concepts that the gardens represented.